2020
DOI: 10.14527/pegegog.2020.011
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of emotional intelligence and marital adjustment in the relationship between mindfulness in marriage and subjective well-being

Abstract: This study examined the mediating role of emotional intelligence and marital adjustment in the relationship between mindfulness and subjective well-being; interpersonal mindfulness in marriage and subjective well-being. 550 married individuals (370 female and 180 male) participated in this research. “Mindfulness Attention Awareness Scale”, “Mindfulness in Marriage Scale”, “Trait Emotional Intelligence Questionnaire-Short Form”, Marital Adjustment Test”, “Positive and Negative Affect Scale”, “Life Satisfaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 90 publications
(327 reference statements)
0
14
1
1
Order By: Relevance
“…Interpersonal mindfulness has recently become an important topic of studies (Frank et al, 2016;Gouveia et al, 2016;Kohlenberg et al, 2015;Parent et al, 2016;Pratscher et al, 2018). Research has found interpersonal mindfulness positively contributes to the interaction process (de Bruin et al, 2014;Duncan, 2007;Duncan et al, 2009;Pratscher et al, 2019) and increases relationship quality (Bogels et al, 2010;Coatsworth et al, 2010;Duncan, 2007;Erus, 2019;Kohlenberg et al, 2015;Pratscher et al, 2018). To illustrate, Duncan (2007) reported that mindfulness in parenting contributes to the quality of parent-child relationships and child management.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Interpersonal mindfulness has recently become an important topic of studies (Frank et al, 2016;Gouveia et al, 2016;Kohlenberg et al, 2015;Parent et al, 2016;Pratscher et al, 2018). Research has found interpersonal mindfulness positively contributes to the interaction process (de Bruin et al, 2014;Duncan, 2007;Duncan et al, 2009;Pratscher et al, 2019) and increases relationship quality (Bogels et al, 2010;Coatsworth et al, 2010;Duncan, 2007;Erus, 2019;Kohlenberg et al, 2015;Pratscher et al, 2018). To illustrate, Duncan (2007) reported that mindfulness in parenting contributes to the quality of parent-child relationships and child management.…”
Section: Discussionmentioning
confidence: 99%
“…This scale only focuses on general interpersonal mindfulness, but it has not yet been adapted to Turkish culture. In conclusion, as a construction of the scale, interpersonal mindfulness is defined in this context, and can be explained as the emergence of the mindfulness level of the individual in a relationship and communicating with other people (Erus, 2019).…”
Section: Define the Constructmentioning
confidence: 99%
See 3 more Smart Citations